A Unifying Hypothesis for Familial and Sporadic Alzheimer's Disease. (14th February 2012) - Proctor, Carole J.; Gray, Douglas A.
Abstract : Alzheimer's disease (AD) is characterised by the aggregation of two quite different proteins, namely, amyloid-beta (A β ), which forms extracellular plaques, and tau, the main component of cytoplasmic neurofibrillary tangles. The amyloid hypothesis proposes that A β plaques precede tangle formation but there is still much controversy concerning the order of events and the linkage between A β and tau alterations is still unknown. Mathematical modelling has become an essential tool for generating and evaluating hypotheses involving complex systems. We have therefore used this approach to discover the most probable pathway linking A β and tau. The model supports a complex pathway linking A β and tau via GSK3 β, p53, and oxidative stress. Importantly, the pathway contains a cycle with multiple points of entry. It is this property of the pathway which enables the model to be consistent with both the amyloid hypothesis for familial AD and a more complex pathway for sporadic forms.